Vision examination protocol for archery athletes along with an introduction to sports vision - Mohammadi, S. F.; Amiri, M. A.; Naderifar, H.; Rakhshi, E.; Vakilian, B.; Ashrafi, E.; Behesht-Nejad, A.-H. (Asian Journal of Sports Medicine, 2016)
Introduction: Visual skills are one of the main pillars of intangible faculties of athletes that can influence their performance. Great number of vision tests used to assess the visual skills and it will be irrational to perform all vision tests for every sport.